Functional Characterisation and Permeation Studies of Lyophilised Thiolated Chitosan Xerogels for Buccal Delivery of Insulin - S. Boateng, Joshua; C. Mitchell, John; Pawar, Harshavardhan; Ayensu, Isaac (Protein and Peptide Letters, 2014)
Stable and mucoadhesive, lyophilised, thiolated chitosan xerogels, loaded with insulin for buccal mucosa deliv- ery, in place of the currently used parenteral route have been developed. The xerogels were backed with impervious ethyl- cellulose laminate to ensure unidirectional release and also loaded with enzyme inhibitor to enhance insulin permeability across the buccal mucosa. Characterisation of xerogels using 1 HNMR confirmed the degree of deacetylation of the syn- thesised thiolated chitosan. The amount of thiol groups immobilised on the modified chitosan was quantified by Ellman’s reaction and molecular weight monitored by gel permeation chromatography. The stability of the secondary structure of insulin was examined by attenuated total reflectance Fourier transform infra-red spectroscopy and circular dichroism. In vitro and ex vivo permeation studies were undertaken by using EpiOral ™ and sheep buccal membrane respectively. Insu- lin released from thiolated chitosan xerogels, loaded with aprotinin (enzyme inhibitor and permeation enhancer) showed a 1.7-fold increase in permeation through EpiOral ™ buccal tissue construct compared to the pure drug. However, permea- tion was decreased for xerogels containing the enzyme inhibitor glutathione. Further, aprotinin containing xerogels en- hanced insulin permeation through sheep buccal membrane and demonstrated good linear correlation with the permeation data from the EpiOral ™ study. The results show the potential application of lyoph ilised thiolated chitosan xerogels con- taining aprotinin with improved mucoadhesion, penetration enhancing and enzyme inhibition characteristics for buccal mucosa delivery of macromolecules such as insulin.
Keywords: enzyme inhibitor